The Right to Life, Liberty and Security for Prostitution: Canada v. Bedford - Snow, Natalie M. (Women & criminal justice, 2023)
Canada v. Bedford (2013) was a Supreme Court case challenging prostitution laws in Canada. Before Bedford, the Criminal Code outlawed certain elements of prostitution. In Bedford, it was argued the current laws violated the Canadian Charter of Rights and Freedoms, which guarantees the right to life, liberty, and security for all. The Supreme Court held that the laws violated the right to security as afforded by Section 7 of the Canadian Charter of Rights and Freedoms. Subsequently, the Canadian government enacted Bill C-36, which criminalized prostitution. Although these laws attempted to extend the rights of sex workers, many argue that Bill C-36 only changes who gets charged with a crime and does not ensure the safety or security of sex workers. This review will discuss the current state of the sex industry in Canada and how these laws impact women working within the industry.